Kinetic of Dissolution of Nickel Limonite Calcine by Sulfuric Acid Solution - Setiawan, Iwan; Nabilah, Annisa; Oediyani, Soesaptri; Subagja, Rudi; Irawan, Januar; Sampoerno, Arief Budi; Yunita, Fariza Eka; Suharyanto, Ariyo; Syahid, Adi Noer (Metalurgi, 2023)
Currently, more than 60% of nickel processing is carried out using nickel sulfide as a raw material. Nonetheless, due to the depletion reserves of nickel sulphide, nickel laterite has drawn a lot of interest to be processed as raw material. Nickel laterite in Indonesia is generally found in low grades, with nickel concentration of <1.15%. One method of treating nickel limonite is leaching in a sulfuric acid solution. This study aims to determine the reaction rate in the leaching process of calcine nickel limonite and the effect of sulfuric acid concentration and leaching temperature on the percent nickel extraction. In this research, the limonite ore from Pomalaa, Southeast Sulawesi, Indonesia, which has undergone a reduction process, was used as raw material. This research was conducted by leaching method on nickel limonite calcine using sulfuric acid reagent with 0.2, 0.5, and 1 M concentration variation, temperature variations of 60, 70, and 90°C, stirring speed 500 rpm, and %S/L (w/w) 10%. In this leaching research, the activation energy obtained at a sulfuric acid concentration of 0.2, 0.5, and 1 M are 13,7379 kJ/mol, 19,7582 kJ/mol, 20,3161 kJ/mol, respectively. The leaching process of nickel limonite calcine was controlled by diffusion. The optimum nickel extraction percentage in this study was 97.45%, obtained at a concentration of 1 M sulfuric acid, temperature of 70 °C, and leaching time of 240 minutes.